The effect of internal pressure on the buckling stress of thin-walled circular cylinders under torsion - Crate, Harold; Batdorf, S. B.; Baab, George W. (National Advisory Committee for Aeronautics, 1944)
The results of a series of tests to determine the effect of internal pressure on the buckling load of a thin cylinder under an applied torque indicated that internal pressure raises the shear buckling stress. The experimental results were analyzed with the aid of previously developed theory and a simple interaction formula was derived.
NACA Wartime Report L-67.
Originally issued as NACA as Advance Restricted Report L4E27 (May 1944).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Cylinders.; Loads (Mechanics); Shear (Mechanics); Buckling (Mechanics); Strains and stresses.; Charts, diagrams, etc.; elektronické knihy; electronic books